Pain in Oral and Maxillofacial Surgery and Implant Dentistry: Types and Management - Selvido, Diane Isabel; Bhattarai, Bishwa Prakash; Rokaya, Dinesh; Niyomtham, Nattisa; Wongsirichat, Natthamet (European Journal of Dentistry, 2021)
Over the years, the pain has been defined numerous times in several ways. In oral and maxillofacial surgery, the occurrence of pain, especially postoperatively, is anticipated. Pain arises as a combination of various processes after tissue damage. Distinct pain experiences in oral surgery were depicted in several previous studies, adding knowledge to the field. The management of these encounters has been suggested over time, improving treatment approaches in the clinical setting. This review aims to understand the pain and its types and intervention in the field of oral and maxillofacial surgery.
Keywords: pain; oral and maxillofacial surgery; surgical intervention; clinical studies; tissue damage